Recognition and attunement in migration research. Issue 1 (March 2021) - Conradson, David
This commentary reflects upon Miriam Tedeschi's (2021) use of Gilbert Simondon's work to examine the lived experience of irregular migrants in Finland. It considers what Simondon's ideas illuminate as well as what they appear to leave relatively unexamined. If we are to understand the lived experience of irregular migrants, it is argued that we need theoretical resources that more fully foreground social and political processes of welcome/unwelcome, recognition/disregard and hospitality/hostility. To the extent that Simondon's work supports only a generalised consideration of such matters, it might usefully be supplemented by perspectives that address them in more depth. In this regard, it is suggested that postcolonial and critical geographical scholarship could enable fuller recognition of and attunement to the complex lived experience of irregular migrants.